Wawasan Kebangsaan dan Kontribusi Beragam - Safiudin, Safiudin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2023)
The objective of this research to find out the effect of moderation attitude with Islamic religion knowledge for the  nation view. The research was conducted in SMA Negeri 5 Depok using 2X2  design involving 60 students chosen by using purposive random sampling. The data analysis and interpretation indicated that: 1. There is  difference in students' high moderation attitude between  students' low moderation attitude, 2. There is  difference in students' high Islamic religion knowledge between  students' low Islamic religion knowledge, 3. There is not interaction between of moderation attitude and Islamic relegion knowledge against the nation view, 4. The students high moderation attitude with high Islamic relegion knowledge not diffrence than students low moderation attitude high Islamic relegion knowledge, 4.The students high moderation attitude and  low Islamic relegion knowledge not diffrence than The students low moderation attitude and low Islamic relegion knowledge.